KARAKTERISTIKPENDERITA KANKER PAYUDARA YANG DIRAWAT INAP DI RUMAH SAKIT UMUM Dr. PIRNGADI MEDAN TAHUN 2016 - Lastiar Christina Marpaung; Rahayu Lubis; Sri Novita Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
ABSTRACT Breast cancer is one of the women’s health problem in Indonesia. Based on esimation Globocan International Agency of research on Cancer in 2012 explain insidens rate breast cancer of 40 per 100.000 women. Based on medical record data from Dr. Pirngadi Hospital medan in 2011-2013 there was 775case of breast cancer which hospitalized. The purpose of this study is to know characteristic of breast cancer in Dr. Pirngadi Hospital Medan in 2016. The research is a descriptive research with case series design. The population totaled to 775 peoples and the sample totaled to 106 people. Data obstained medical records, data analyzed by Chi-Square and Mann-Whitney. The result show the highest proportion of breast cancer patients at the age of 47-52 years (27,3%), women (100%), senior high school (76%), Islam (66,7%), Javanese (51,3%), housewife (62,0%), married (80,0%), residence outside Medan (75,3%), the main complainment of lumps in breast area (39,3%), stage IIIB (32,7%), BPJS (99,3%), chemoterahphy (76,7%), average length of stay 5 days, home ambulatory (58,0%). The result of statistical test show there was a difference average length of stay of breast cancer patients based on treatment. There was no difference betwen proportion of age by clinical stage, the medical management by the clinical stage, the average treatment duration by clinical stage, medical management by the circumtance when returning home, medical management by the source of cost, clinical stage by the circumtance when returning home. Women aged 25 years are advised to perform breast self-examination and checking her self to the hospital or a doctor if find a lump in breast area. Dr. Pirngadi general hospital Medan is suggested to complete the breast cancer patient status card include family history of disease sufferers. Keyword : Breast Cancer, Characteristics, DR Pirngadi Hospital